Aplikasi Game Balap Sepeda Ontel Berbasis Android - Muh. Rifli Aris; Ade Hastuty; Mughaffir Yunus; Muhammad Basri; Ahmad Selao (Jurnal Sains dan Ilmu Terapan, 2025)
Traditional games are part of cultural heritage that contain historical and educational values. One example is the ontel bicycle, a classic bicycle still widely known among Javanese people as the "kebo bicycle." However, along with the development of technology and modern lifestyles, the younger generation's interest in traditional games has decreased. This condition encourages the need for an alternative approach to reintroduce the ontel bicycle to the current generation. This study aims to design and develop an Android-based ontel bicycle racing game that is educational and supports cultural preservation. The research method used in the development process uses the Unity platform, while the testing phase was conducted using black box and white box methods. Based on the test results, the application runs according to the designed logic and no logical errors were found, with a cyclomatic complexity of V(G) = 3. This game application is equipped with a main menu, game levels with various difficulty levels, and information about the developer.